El sureste de la ciudad de México, 1524-1542: Grupos de poder y articulación socioespacial entre españoles e indígenas - Rovira-Morgado, Rossend; Ramírez Méndez, Jessica (Jahrbuch für Geschichte Lateinamerikas, 2021)
The paper deals with a project of social organization developed in the south-eastern sections of Mexico City during the two decades following the Conquest. It focuses on the collaboration of specific personalities of the indigenous nobility with both Spanish governmental institutions and secular clergymen. Empirical evidence suggests that this collaboration was opposed to the project of evangelization of the medicant friars during the 1520s and 1530s. As a result the article questions the assumption historiography has established in the 16th century according to which Spanish and Indian secular and religious communities were already segregated in that early period.
Keywords: Mexico City; Spanish-Indigenous Interactions; Bishop's Houses; Hermitage of the Tailors; Casas de Tapia; San Pablo; Beaterio